HbA1c levels in patients of acute decompensated heart failure - Shekhar, Ravi; Govind, Biju; Chowdary, NVS; Sharma, Sadhna; Satish, R John; Desai, S Vidya; Prabodh, V Siva; Aslami, Ahmad Nadeem (Asian Journal of Medical Sciences, 2016)
Background: Hospitalization for Heart Failure (HF) is increasing in India. Diabetes Mellitus (DM) is closely related to HF. Hb1Ac is an index of metabolic control of DM. Hb1Ac is associated with increased risk of Acute Decompensated Heart Failure (ADHF). The relation between Hb1Ac and ADHF is less well defined. Aims and Objectives: The aim of the study was to find out the prevalence of ADHF among patients admitted for cardiac complaints and to investigate Hb1Ac levels in confirmed patients. Materials and Methods: A hospital based study was conducted at NRI Heart Centre, NRI General Hospital, Guntur from May to July 2013 after institutional ethical approval. All patients of ADHF were included in the study. Patients were analysed for HbA1c. Results: Out of 1147 patients admitted in Coronary Care Unit, there were 101 cases of ADHF giving a prevalence of 8.8%. The mean age was found to be 54.69 years. 19.8% of the patients were of age less than 40. There were 74.3% males and 25.7% females. The mean HbA1c in non diabetic, pre-diabetic and diabetic was 5.32%, 6.0% and 8.45% respectively. Conclusion: Elevated HbA1c is associated with increased morbidity in the heart failure and efforts should be made to treat these patients with proven therapies to lower the blood glucose levels. Asian Journal of Medical Sciences Vol.7(4) 2016 55-58